THE EFFECT OF MILK THISTLE ON INGUINAL LYMPH NODES IN RHEUMATOID ARTHRITIS IN RATS (Western European Journal of Medicine and Medical Science, 2026)
The effect of milk thistle (Silybum marianum) extract on the morphology and morphometry of inguinal lymph nodes in white rats with experimental rheumatoid arthritis was investigated. In arthritis, follicular destruction, sinus dilation, plasmacytic infiltration, and structural disorganization were observed. Biocorrection with milk thistle extract promoted restoration of lymph node architecture, activation of lymphocyte proliferation, reduction of inflammation, and normalization of microcirculation. Morphometric parameters — including lymph node diameter, thickness of cortical and paracortical zones, number and size of follicles, percentage of germinal centers, area of the medullary zone, and stromal volume — demonstrated significant improvement. Milk thistle proved to be an effective natural biocorrector supporting immune activity and reducing morphostructural alterations in rheumatoid arthritis.